At Plattsburg - French, Allen, 1870-1946 (Salt Lake City, UT : Project Gutenberg, 2008)
"At Plattsburg" by Allen French is a novel written in the early 20th century, specifically during the time surrounding World War I. The story revolves around the experiences of Richard Godwin, a naive but earnest citizen, as he navigates military training at a camp in Plattsburgh, New York. The narrative captures his interactions with fellow recruits, including the wealthy David Ridgway Farnham, as they adapt to military life amidst their personal struggles with social class differences and the underlying currents of impending war. The beginning of "At Plattsburgh" sets the stage for Richard Godwin's journey as he arrives at the training camp. Through his letters to his mother, we see his blend of excitement and trepidation about his new life in uniform, marked by encounters with a pacifist pastor and the lively, often humorously portrayed dynamics with fellow recruits. Among them, David Farnham stands out with his upper-class background, creating tension primarily due to his sheltered nature and lack of practical skills. The opening chapters establish the camaraderie, challenges, and transformative experiences of these young men as they confront both the rigors of military training and their own identities during a pivotal time in history. (This is an automatically generated summary.)
Release date is 2008-06-17
E-text prepared by Roger Frank and the Project Gutenberg Online Distributed Proofreading Team
Keywords: New York (State) -- Fiction; Military education -- Fiction; Military Training Camp for Business and Professional Men (Plattsburgh, N.Y.)